2011
DOI: 10.17660/actahortic.2011.900.8
|View full text |Cite
|
Sign up to set email alerts
|

Flurprimidol Preplant Bulb Soaks Control Growth of Potted Liliums

Abstract: In a series of experiments, flurprimidol (Topflor, SePRO Inc., Carmel, Indiana, USA) was applied as a preplant bulb soak to determine its efficacy on growth control of 'Star Gazer' oriental lily (Lilium hybrids), 'Nellie White' Easter lilies (Lilium longiflorum), and vigorously growing tiger lilies (Lilium lancifolium). Emergence date was noted, and the plants were measured at bloom for plant height, plant diameter, and flower number. Optimal concentrations varied by species. Preplant bulb soaks of flurprimido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…While we have found no literature reporting the use of flurprimidol substrate drenches for controlling height of easter lily, previous reports have demonstrated the effectiveness of flurprimidol using a variety of application methods on lilies (Krug et al, 2005a;Pobudkiewicz and Nowak, 1992;Pobudkiewicz and Treder, 2006;Whipker, 2004;Whipker et al, 2011). Krug et al (2005a) reported that applying 0.5 mg flurprimidol per pot provided commercially acceptable height control for 'Star Gazer' oriental lilies with no significant effect on time to anthesis or flower bud number.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…While we have found no literature reporting the use of flurprimidol substrate drenches for controlling height of easter lily, previous reports have demonstrated the effectiveness of flurprimidol using a variety of application methods on lilies (Krug et al, 2005a;Pobudkiewicz and Nowak, 1992;Pobudkiewicz and Treder, 2006;Whipker, 2004;Whipker et al, 2011). Krug et al (2005a) reported that applying 0.5 mg flurprimidol per pot provided commercially acceptable height control for 'Star Gazer' oriental lilies with no significant effect on time to anthesis or flower bud number.…”
Section: Resultsmentioning
confidence: 82%
“…Similarly, height of 'Mona Lisa' oriental lilies was less than untreated plants when flurprimidol was applied as a foliar spray once or twice at concentrations ranging from 10 to 40 mgÁL -1 when shoots were 7 or 14 cm tall (Pobudkiewicz and Treder, 2006). Whipker et al (2011) reported that while preplant bulb soaks in flurprimidol solutions were effective in suppressing stem elongation of 'Nellie White' easter lilies, however variation in responses year-to-year and among different bulb lots made it difficult to identify a recommendation for bulb soak concentration for commercial production. However, flurprimidol bulb soaks have been reported to be a viable PGR application to control height of other lily species and cultivars (Krug et al, 2005a, Whipker et al, 2011.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations